Editorial: (Re)inventing Futures for Information Design - Kelli C.A.Silva Smythe; Farias, Priscila Lena (InfoDesign, 2026)
The 12th edition of CIDI – Information Design International Conference featured the theme “Informing and (Re) Creating Futures”. This special issue of InfoDesign brings together papers featured at the event and selected through evaluation by the conference reviewers and the journal’s editors. The issue also includes articles prepared by the event’s keynote speakers. The work published here collectively consolidate Information Design as a mature discipline capable of articulating ethics, social justice, and innovation.